2015
DOI: 10.1021/acsami.5b06604
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Ensemble Based on Bispyrene Fluorophore and Surfactant Assemblies: Sensing and Discriminating Proteins in Aqueous Solution

Abstract: A particular bispyrene fluorophore (1) with two pyrene moieties covalently linked via a hydrophilic spacer was synthesized. Fluorescence measurements reveal that the fluorescence emission of 1 could be well modulated by a cationic surfactant, dodecyltrimethylammonium bromide (DTAB). Protein sensing studies illustrate that the selected ensemble based on 1/DTAB assemblies exhibits ratiometric responses to nonmetalloproteins and turn-off responses to metalloproteins, which can be used to differentiate the two typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 48 publications
0
26
1
Order By: Relevance
“… 52 However, the discrimination ability is highly dependent on the number of employed sensor elements, and usually in the case of fluorescent sensor arrays, different fluorophores are commonly employed to provide the cross-reactivity that leads to the complexity of data collection which requires scanning the emission spectra of all of the sensor elements or may even require different excitation wavelengths for each of the sensor element. 53 However, in the present case, we realized that interestingly arginine shows a distinct fluorescence behavior than lysine, when compared at the identical concentration. For example, arginine displays a more prominent emission intensity at blue-shifted wavelength when compared with lysine ( Figures 6 A and S6, Supporting Information ).…”
Section: Resultscontrasting
confidence: 42%
“… 52 However, the discrimination ability is highly dependent on the number of employed sensor elements, and usually in the case of fluorescent sensor arrays, different fluorophores are commonly employed to provide the cross-reactivity that leads to the complexity of data collection which requires scanning the emission spectra of all of the sensor elements or may even require different excitation wavelengths for each of the sensor element. 53 However, in the present case, we realized that interestingly arginine shows a distinct fluorescence behavior than lysine, when compared at the identical concentration. For example, arginine displays a more prominent emission intensity at blue-shifted wavelength when compared with lysine ( Figures 6 A and S6, Supporting Information ).…”
Section: Resultscontrasting
confidence: 42%
“…23 As a different strategy, our group has made efforts using surfactant assemblies to encapsulate and modulate uorophores to develop sensitive and discriminative sensors for proteins. [24][25][26] In our rst try, we found that cationic surfactant DTAB assemblies could well modulate the uorescence emission of a cholesterol-modied pyrene-based uorophore that was highly aggregated in aqueous solution. This modulation effect could be further used to sense the protein-induced assembling variation of surfactants and realized the selective detection of two negatively charged nonmetalloproteins.…”
Section: Introductionmentioning
confidence: 78%
“…The use of a surfactant is ideal for stabilizing the dispersed form of a molecule . The modulating effect of sodium dodecylbenzenesulfonate (SDBS) on the aggregation of PEPBI was evaluated in aqueous solution.…”
Section: Resultsmentioning
confidence: 99%